Patent law and standardisation - managing IP rights for green technologies - Mamysheva,Dzhamilia (2023)
The development of the new green industries based on standards creates legal issues of the collision between patent law and standardisation processes. Whereas some solutions have already been implemented in the industries like telecommunications, it is of an interest to research on whether these solutions might be used when managing intellectual property rights in the green technologies or there will be a shift in the policies. The thesis is aimed at describing and analysing the legal issue of the possible collision between patent law and standardisation systems in the process of the dissemination of green technologies and eco-innovations. This is done by answering the certain research questions on the role of the EU legal framework on standardisation in the technology transfer, the positive and negative consequences of the interaction between patents and standards, on the position of patent law on standardisation and possible solutions to this legal issue. To fulfill the purpose a legal dogmatic method with systematic analysis of existing case law, legislation and literature from intellectual property (IP) scholars is used, it is also complemented with the wide analysis of Commission’s proposals, the opinion of the practitioners, the legal documents of the leading industry players.
Keywords: Patent law; standardisation; green technology; standard essential patents; FRAND.